The Value of Nuclear Medicine Versus Ultrasonography in Diagnosing Renal Disease - Mohammed, Salman A; Alamoudi, Omar M; Bafaraj, Saeed M (International Journal of Medical and Health Sciences Research, 2017)
Objective: The study aims to assess the value of nuclear medicine and ultrasonography for diagnosing renal diseases among patients of different ages. Method: Quantitative analysis has been opted for evaluating the effectiveness of both imaging modalities for the diagnosis of renal diseases. 80 patients were targeted, who were having renal disease indications and they were diagnosed through modalities. The outcomes of both imaging techniques were compared through data analysis. Results: Positive findings of the nuclear medicine were observed between the age groups 0-12 years (58.1%), 13-24 years (16.1%), 25-36 years (1.6%), 37-48 years (9.7%), 61-72 years (3.1%) and 73-84 (8.1%) years of patients. Concerning the ultrasonography technique, positive effects were observed among the patients of age-group 0-12 years (58.7%), 13-24 years (17.5%), 25-36 years (3.2%), 49-60 years (3.2%) and 73-84 years (3.2%). The sensitivity rate for nuclear medicine was 100% as compared to ultrasonography, which was 93.6%. However, the specificity and accuracy rates for nuclear medicine were 78.4%, and 21.5%; however, similar rates for ultrasonography were 79.7%, and 13.92%, which showed better outcomes of ultrasonography. Conclusion: Ultrasonography was observed showing positive results among all age groups as compared to nuclear medicine imaging modalities. Future studies must focus on other imaging techniques to timely diagnose the disease and initiate the treatment before it get worse.